2022
DOI: 10.1002/pro.4296
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic antibodies block receptor binding and current‐inhibiting effects of α‐cobratoxin from Naja kaouthia

Abstract: Each year, thousands of people fall victim to envenomings caused by cobras.These incidents often result in death due to paralysis caused by α-neurotoxins from the three-finger toxin (3FTx) family, which are abundant in elapid venoms. Due to their small size, 3FTxs are among the snake toxins that are most poorly neutralized by current antivenoms, which are based on polyclonal antibodies of equine or ovine origin. While antivenoms have saved countless lives since their development in the late 18th century, an op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In this study, we developed a prototype mixture based on cross-neutralizing V H Hs and demonstrated its ability to neutralize lethality induced by two North American coral snake venoms in a mouse model. Previous studies have shown that a single monoclonal antibody can neutralize the lethal effects of snake venom when lethality is caused by one predominant toxin 39 , 40 , that such antibodies can be further developed to become broadly-neutralizing 19 , and that oligoclonal antibodies can be used to neutralize multiple different toxins 18 . However, here, we go beyond the state of the art by demonstrating that the concepts from these previous studies can be merged and applied to a simpler antibody format, namely the V H H format, thereby providing a proof of concept for a different type of antivenom 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we developed a prototype mixture based on cross-neutralizing V H Hs and demonstrated its ability to neutralize lethality induced by two North American coral snake venoms in a mouse model. Previous studies have shown that a single monoclonal antibody can neutralize the lethal effects of snake venom when lethality is caused by one predominant toxin 39 , 40 , that such antibodies can be further developed to become broadly-neutralizing 19 , and that oligoclonal antibodies can be used to neutralize multiple different toxins 18 . However, here, we go beyond the state of the art by demonstrating that the concepts from these previous studies can be merged and applied to a simpler antibody format, namely the V H H format, thereby providing a proof of concept for a different type of antivenom 41 .…”
Section: Discussionmentioning
confidence: 99%
“…As a representative long-chain α-neurotoxin, we chose α-cobratoxin from Naja kaouthia, one of the most extensively characterized toxins from the 3FTx family 43 (Figure 1). From 42 RFdiffusion designs against α-cobratoxin, one candidate had a binding affinity of 1.3 µM using BLI (Supplementary Figure S3).…”
Section: Design Of α-Neurotoxin Binding Proteinsmentioning
confidence: 99%
“…The following method was adapted from Fitch et al [24] and Wang et al [25] and, as in section 2.2, all reagents were acquired from Gibco, Thermo Fisher Scientific, Paisley, UK, unless stated otherwise. One vial of FLIPR membrane potential dye (Component A, Explorer Kit Blue, R8042, Molecular Devices, San Jose, CA, USA) was dissolved in 36 mL assay buffer to create the dye solution.…”
Section: Membrane Potential Assay Of Nachr Activationmentioning
confidence: 99%
“…Wang et al [25] previously demonstrated antagonism by α-BgTx, a Lc-α-NTx isolated from the venom of B. multicinctus, to the nicotine response of TE671 cells using membrane potential dye [32]. Consequently, α-BgTx was used along with a commercially available Sc-α-NTx, namely sNTx1 from the venom of N. pallida, which was used in previous studies to investigate Sc-α-NTx activity on nAChRs under the name 'toxin α' and originally thought to be isolated from venom of N. nigricollis [46].…”
Section: Nachr Agonists Produce Fluorescent Responses In Te671 Cells ...mentioning
confidence: 99%
See 1 more Smart Citation